2021
DOI: 10.33166/acdmhr.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Resource Practices and Organizational Commitment on Employee Performance

Abstract: The aim of this analysis is to examine the effect of HRM practices and organizational commitment on employee performance in the Bahrain Cement Industry. This research used a convenience sampling tool to obtained data from 315 respondents through a self-administered questionnaire. The proposed structural model was also tested using variance-based partial least structural equation modelling (PLS-SEM). The findings of this study showed that all HRM practices and organizational commitment have a significant and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The role of HR is recognised at all levels and stages. Consequently, one of the organisation's pillars is human resources [12]. HRM is essential for management because its deals with the organisation's most precious resource, which is known as HR [4].…”
Section: Human Resource Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The role of HR is recognised at all levels and stages. Consequently, one of the organisation's pillars is human resources [12]. HRM is essential for management because its deals with the organisation's most precious resource, which is known as HR [4].…”
Section: Human Resource Practicementioning
confidence: 99%
“…One of the crucial responsibilities of HR is to manage employees in the organisation and their practice should be in line with the organisational plan [17]. Mainly because without human resources, an organisation's resources cannot be managed and developed [12]. To gain a competitive advantage, the majority of organisations have been focusing on their HRM practices and how they respond to global problems [18].…”
Section: Human Resource Practicementioning
confidence: 99%
“…The loss of skilled employees can lead to an increased workload and reduced job security, resulting in decreased motivation and productivity. Another study found that employee poaching can lead to decreased employee commitment and increased turnover rates, resulting in high costs for firms regarding recruitment and training [22].…”
Section: Employee Poaching and Employee Productivitymentioning
confidence: 99%
“…This research aims to determine the effect of the application of human resource management practices and organizational commitment on employee performance in the Bahrain cement industry, and the results of this research show that the application of human resource management and work commitment has a significant effect and positive towards employees. 14 Research with a survey of publications in the Web of Science database is used to investigate the problem under study, t he the purpose of this paper is to explore the possibility of appropriate curriculum adaptation given the trends of human capital development in the context of digitalization. 15 Research on the influence of talent management and organizational culture on employee productivity in the public sector also assessed the moderate effects of employee engagement in such relationships.…”
Section: Introductionmentioning
confidence: 99%